The Degree of Mucosa-Associated Microecological Imbalance in Ulcerative Colitis Patients with Different Mayo Score and Its Relationship with Mucosal Mechanical Barrier Damage - Shang, Yansheng; Wang, Xiaohong; Diao, Xingyuan; Li, Lixiang; Zuo, Xiuli (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Ulcerative colitis (UC) is a chronic inflammatory bowel disease known for mucosal inflammation and dysbiosis of gut microbiota. The association between mucosa-related microecological imbalance and UC severity is a crucial aspect in unraveling the disease’s pathogenesis. The relationship between mucosa-related microecological imbalance and different levels of UC severity was investigated, as defined by Mayo score, and its association with mucosal mechanical barrier damage. Materials and Methods: The composition of mucosa-associated bacterial and fungal populations in UC patients and healthy controls was analyzed using Illumina MiSeq sequencing. The analysis focused on changes in the diversity of bacteria and fungi, along with their distribution at phylum and genus levels. Additionally, the potential relationship between microecological imbalance and damage to the mucosal mechanical barrier was assessed. Results: Patients with severe UC exhibited elevated abundance indexes, increased numbers of phyla, and higher proportions of specific phyla (Actinobacteria, Acidobacteria, Chloroflexi, Gemmatimonadetes, Nitrospirae, and an unclassified phylum) compared to patients with mild or moderate UC. Conversely, the proportions of dominant bacterial phyla (Firmicutes, Bacteroidetes, and Proteobacteria) displayed an inverse relationship with UC severity. In the fungal microbiota, moderate and severe UC cases showed a greater prevalence of negative genera compared to mild cases. Notably, changes in microflora composition were associated with the extent of mucosal mechanical barrier damage. Conclusion: The progression of mucosa-associated microecological imbalance is associated with increasing inflammation in UC, potentially contributing to disruptions in the intestinal mucosal mechanical barrier. Cite this article as: Shang Y, Wang X, Diao X, Li L, Zuo X. The degree of mucosa-associated microecological imbalance in ulcerative colitis patients with different mayo score and its relationship with mucosal mechanical barrier damage. Turk J Gastroenterol. Published online October 9, 2025. doi:10.5152/tjg.2025.24609